AKTIVITAS ANTIKOLESTEROL EKSTRAK ETANOL BUAH KIWI HIJAU (Actinidia deliciosa) - Novena Yety Lindawati; Desi Widya Ningsih (Jurnal Ilmiah Manuntung, 2020)
Disease in the liver caused by hypercholesterolemia is fatty liver. Fatty liver is one of the damages to the liver, a condition in which the liver experiences fat accumulation. Green kiwifruit (Actinidia deliciosa) is a plant that contains a lot of flavonoid compounds can be used as cholesterol-lowering. Flavonoids are able to release cholesterol found in the walls of blood vessels and organs in the body. The purpose of this study was to determine the presence or absence of anticholesterol activity and EC50 values in ethanol extracts of green kiwifruit (Actinidia deliciosa) with a concentration series of 2.5; 5.0; 7.5; 10.0; 12.5 ppm. Ethanol extract of green kiwifruit was tested for active substance content and quantitative analysis using UV-Vis spectrophotometry method at a wavelength of 668 nm and operating time of 15 minutes. The results showed ethanol extract of green kiwifruit contains phenols, flavonoids, saponins, vitamin C which can reduce cholesterol levels with an average EC50 value of 7.3 ppm with a coefficient of variation value of 1.12%. Keywords : Cholesterol, Lieberman-burchard, Extract, Green kiwifruit (Actinidia deliciosa), UV-VIS spectrophotometry.